Surgical treatment of gastric cancer - Hsu, Jun-Te; Yeh, Ta-Sen; Jan, Yi-Yin (Digestive Medicine Research, 2018)
Gastric cancer (GC) is the fourth most common cancer and the third leading cause of cancer-related deaths worldwide (1). Most patients have inoperable disease at the time of diagnosis and encounter recurrence even after radical surgery (2). Curative resection including adequate lymphadenectomy provided the chance of a cure for localized disease (2,3).